Psycholinguistics of Reading In Foreign Language Contexts: A Comprehensive Overview - Rustamovna, Kadirova (Indonesian Journal Publisher, 2025)
This article provides a comprehensive overview of the psycholinguistics of reading in foreign language contexts, with a particular focus on second language (L2) reading. It explores the role of reading in language acquisition, emphasizing its importance for learners of English as a second language (ESL) in higher education. The paper highlights key psycholinguistic theories and cognitive mechanisms involved in L2 reading comprehension, including those by scholars like Goodman, Smith, Koda, and Grabe. The research underscores the significance of integrating both lower-level (decoding) and higher-level (critical analysis) cognitive skills for successful comprehension. It also examines how language transfer, memory, attention, and digital tools influence the reading process. Recent trends in reading research, including the impact of technology and bilingualism, are discussed, showing how digital tools can enhance ESL reading skills. The article calls for the development of effective, personalized reading strategies that combine cognitive insights and interactive, technology-based methods to improve reading proficiency and academic success for ESL students.